Implementasi Algoritma K-Medoids untuk Pengelompokkan Sebaran Mahasiswa Baru - Irawan, Eka; Siregar, Sandy Putra; Damanik, Irfan Sudahri; Saragih, Ilham Syaputra (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The existence of new students at a tertiary institution is a routine activity every year in a tertiary institution and can also see the sustainability of the tertiary institution. The variety of regional origin of new students makes the party from the university want to see the distribution of new students based on the origin of the school and its place of residence. STIKOM Tunas Bangsa is one of the tertiary institutions in Pematangsiantar. It aims to promote the university. K-Medoids is able to group data on the distribution of new students in STIKOM Tunas Bangsa Pematangsiantar. The clusters produced in this study are of three clusters. The validity used in this study is the validity of Silhoutte Coefficient. The validity value generated in the K-Medoids algorithm produces a validity value of -116.47 by assuming that if the non-medoids value produced S